Optimization of Microwave Vacuum Drying and Ultrasonic Extraction on Physicochemical Properties of Butterfly Pea Flower (Clitoria ternatea L.) - Makha, Panruthai -; Sriwattana, Sujinda (Science Essence Journal, 2020)
Optimization of Microwave Vacuum Drying and Ultrasonic Extraction on Physicochemical Properties of Butterfly Pea Flower (Clitoria ternatea L.) The objectives of this study were to optimize drying process of butterfly pea flower (BPF) using microwave vacuum and to optimize ultrasonic extraction condition of dried BPF. BPF was dried at different microwave power (3,600 W and 4,800 W) and different times (15, 20 and 25 min). The optimum condition of drying was microwave power 3,602.05 to 4,537.65 W and drying time 16.80 to 23.17 min. The significant (p≤0.05) parameters on the drying efficiency were yield, moisture, aw, total anthocyanin content (TAC), L*, a*and b* as 17.50%, 10.20%, 0.389, 1.09 mg/g DW, 43.39, -0.78 and 0.87 respectively. Dried BPF was extracted using ultrasonic extraction (solvent: water and ethanol, extraction temperature: 35 ºC and 45 ºC, extraction time: 25 and 30 min). The optimum condition of water extraction was 35.10 to 44.93 ºC for 26.67 to 29.97 min. The optimum condition of 50% ethanol extraction was temperature 37.86 to 44.94 ºC and extraction time 25.34 to 29.99 min. BP extract could be used in food and cosmetic industries. สภาวะที่เหมาะสมในการอบแห้งด้วยไมโครเวฟสุญญากาศและการสกัดด้วยคลื่นอัลตราโซนิกต่อสมบัติทางเคมีกายภาพของดอกอัญชัน (Clitoria ternatea L.) งานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาสภาวะการอบแห้งที่เหมาะสมของดอกอัญชันโดยใช้ไมโครเวฟสุญญากาศ และศึกษาสภาวะที่เหมาะสมในการสกัดดอกอัญชันอบแห้งโดยใช้คลื่นอัลตราโซนิกเพื่อนำมาพัฒนาผลิตภัณฑ์สารให้สีธรรมชาติ นำดอกอัญชันมาอบแห้งด้วยไมโครเวฟสุญญากาศที่ระดับพลังงาน 3,600 และ 4,800 วัตต์ และใช้เวลา 15 20 และ 25 นาที พบว่าช่วงที่เหมาะสมในการอบแห้งจะใช้พลังงานของไมโครเวฟที่ 3,602.05-4,537.65 วัตต์ และใช้เวลาในการอบ 16.80 - 23.17 นาที จากการวิเคราะห์ดอกอัญชันอบแห้งมีร้อยละผลผลิต ปริมาณความชื้น ค่าวอเตอร์แอกทิวิตี ปริมาณแอนไซยานิน และค่าสี L*, a* และ b* เท่ากับ 17.50, 10.20, 0.389, 1.09 มิลลิกรัมต่อกรัม, 43.39, -0.78 และ 0.87 ตามลำดับ จากนั้นทำการสกัดดอกอัญชันอบแห้งโดยใช้คลื่นอัลตราโซนิกด้วยตัวทำละลายที่ ใช้คือน้ำกลั่นและเอทานอล อุณหภูมิที่ใช้ 35 และ 45 องศาเซลเซียส และระยะเวลา 25 และ 30 นาที พบช่วงที่เหมาะสมในการสกัดที่ใช้น้ำกลั่นที่อุณหภูมิ 35.10 - 44.93 องศาเซลเซียส และใช้เวลา 26.67- 29.97 นาที ส่วนช่วงที่เหมาะสมในการสกัดใช้เอทานอลที่ความเข้มข้นร้อยละ 50 เป็นตัวทำละลายได้แก่อุณหภูมิ 37.86 - 44.94 องศาเซลเซียส ใช้เวลาการสกัด 25.34 - 29.99 นาที สารสกัดดอกอัญชันสามารถประยุกต์ในอุตสาหกรรมอาหารและเครื่องสำอางได้